Determinants of Health Worker Performance at West Sidoarjo Regional Hospital - Fibriany, Hary Indah; Imam, Sentot; Peristiowati, Yuly; Anam, Agus Khoirul; Andi Hayyun Abiddin, Andi (Journal of Ners and Midwifery, 2026)
Recently, health workers who have poor performance or fall below expectations have been targeted, especially health workers. One of the causes is the level of discipline of health workers, which is still lacking. The objective of this study was to analyze the influence of work discipline, compensation, employee status, and organizational commitment on the performance of health workers at West Sidoarjo Regional Hospital. This study was quantitative research with independent variables consisting of work discipline, compensation, health worker status, organizational commitment, and health worker performance as the dependent variable. The population in this study was health workers at Sidoarjo Barat Regional Hospital, totaling 289 people. Through a simple random sampling technique, a sample of 168 respondents was obtained. This research was conducted from February to April 2025 at Sidoarjo Barat Regional Hospital, East Java, Indonesia. A questionnaire was used to collect data. Data were analyzed using multiple linear regression. This study showed the influence of work discipline on the performance of health workers, obtaining a t-count value of 5.828 with a significant value of 0.004 < 0.05. On the other hand, the influence of compensation on the performance of health workers obtained a t-count value of 131.529 with a significant value of 0.000 < 0.05. However, the influence of employee status on the performance of health workers obtained a t-count value of -0.766 with a significant value of 0.445 < 0.05, and the influence of organizational commitment on the performance of health workers obtained a t-count value of 4.865 with a significant value of 0.003 < 0.05. Work discipline, compensation, employee status, and organizational commitment are combined simultaneously; they will affect the performance of health workers, but if the variables are separated one by one and then linked to the influence on the performance of health workers, then there is one variable that statistically does not affect.